Analisis Model Bisnis Fintech Payment Syariah Berbasis Zakat dan Wakaf - Cicih Maryati; Amelia Kartika (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2025)
Through literature studies and case analysis, this research in-depth examines the sharia fintech business model based on zakat and waqf. This research identifies potential, challenges, and provides policy recommendations to support the growth of this business model. The research results show that this business model has great potential in increasing financial inclusion and expanding the reach of beneficiaries. This research aims to examine how sharia fintech can contribute to improving social welfare through more effective management of zakat and waqf